2003
DOI: 10.1159/000074205
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of the Respiratory Function and Control of Ventilation in Patients with Anorexia nervosa

Abstract: Background: Anorexia nervosa is a good model to study the effects of malnutrition on the respiratory system, since it excludes the consequences that some chronic diseases can have on the lung. Objective: The objective of this study was to assess pulmonary function and alterations in the respiratory system in patients with anorexia nervosa. Methods: Twenty-two women, 12 with anorexia nervosa and 10 healthy volunteers, were studied. Anthropometric data were gathered for all the participants. In every case, an ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 8 publications
(10 reference statements)
3
26
1
Order By: Relevance
“…30 Our patient group also demonstrated a significant improvement in MNHR and in orthostatic heart rate changes during hospitalization as seen in other studies. 31 The respiratory acidosis found in our study could result from several physiological mechanisms that have been described in patients with AN: impairment of the respiratory muscle strength and performance, in particularly diaphragmatic function, [13][14][15][16][17][18][19] adverse effects on control of breathing, 14,20 and possible alterations of lung structure (emphysemalike changes). [21][22][23][24][25] Gonzalez-Moro et al, 14 in a study looking on respiratory function and control of ventilation in 12 women with AN, found that they had normal blood gases at baseline and presented a slower and more superficial respiratory pattern compared to a control group.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…30 Our patient group also demonstrated a significant improvement in MNHR and in orthostatic heart rate changes during hospitalization as seen in other studies. 31 The respiratory acidosis found in our study could result from several physiological mechanisms that have been described in patients with AN: impairment of the respiratory muscle strength and performance, in particularly diaphragmatic function, [13][14][15][16][17][18][19] adverse effects on control of breathing, 14,20 and possible alterations of lung structure (emphysemalike changes). [21][22][23][24][25] Gonzalez-Moro et al, 14 in a study looking on respiratory function and control of ventilation in 12 women with AN, found that they had normal blood gases at baseline and presented a slower and more superficial respiratory pattern compared to a control group.…”
Section: Discussionmentioning
confidence: 91%
“…On the contrary, several investigators reported blood gases within the normal range. 11,14,17 It was suggested that the reduction in oxygen consumption and in pCO 2 production and energetic output present in subjects with AN can delay the onset of hypercapnia. 20,34 Furthermore, it has been assumed that hypercapnia does not generally appear before the respiratory muscular force reaches a value inferior to 30% of its predicted value.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations